Assessment of Chemical Disinfectants Efficacy against Escherichia coli Biofilm Developed on Glass and Wood at Refrigeration and Room Temperatures - Anas Muazu, Nor Iza A. Rahman, Umar Faruk Abdullahi, Sani Aliyu, Jonathan Ajisafe Ogidi, Ahmed Faruk Umar (Journal of Applied Pharmaceutical Science, 2015)
Objectives: The aim of this work was to study the formation of biofilm on glass and wood coupons at refrigeration and room temperatures, different incubation periods and to assess the efficacy of hydrogen peroxide (HP), Para Acetic Acid (PAA), Sodium hypochlorite (SH) and mixture of PAA + SH against the biofilm. Method:200 µL of 108suspension E. coli ATCC 29922 was inoculated on the coupons inside petri dishes containing 20 ml of tryptic soy broth, incubated at 10 and 270C for 24, 48, 72 and 168 hours. Biofilm developed at each hour above was quantified by bead-vortex followed by agar plating. The action of disinfectants was tested on 168 hours biofilm. The surfaces were exposed to the disinfectants and incubated at 27 °C for 10 minutes, followed by deactivation for 5 minutes. Cells that resisted disinfectants effect were vortexed and enumerated by agar plating. Results: The results showed that E. coli can develop high biofilm on wood apart from glass. After disinfection treatment, HP had the highest efficacy at 27°C followed by PAA then SH, whilst PAA + SH had the least.Conclusion: It can be concluded that HP and PAA can be good disinfectants agents against E. coli biofilm.
Keywords: Biofilm, E. coli, Log Reduction, Survival Fractions.